Structure of a human intramembrane ceramidase explains enzymatic dysfunction found in leukodystrophy - Ieva Vasiliauskaité-Brooks (Nature Portfolio, 2018)
Alkaline ceramidases (ACERs) are a class of poorly understood transmembrane enzymes controlling the homeostasis of ceramides. Here authors solve the Xray structure of human ACER3 and uncover a Ca2+ binding site providing an explanation for the known regulatory role of Ca2+ on ACER3 activity.